2019
DOI: 10.1101/691030
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parkinson’s disease-associated alterations of the gut microbiome can invoke disease-relevant metabolic changes

Abstract: 25 26 Parkinson's disease (PD) is a systemic disease clinically defined by the degeneration of 27 dopaminergic neurons in the brain. While alterations in the gut microbiome composition have 28 been reported in PD, their functional consequences remain unclear. Herein, we first analysed 29 the gut microbiome of patients and healthy controls by 16S rRNA gene sequencing of stool 30 samples from the Luxembourg Parkinson's study (n=147 typical PD cases, n=162 controls). 31All individuals underwent detailed clinica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 86 publications
(117 reference statements)
2
24
0
Order By: Relevance
“…Among the most abundant taxa in PD there were bacteria belonging to the Christensenellaceae family (Fig 5, Supplementary Figure 10, 11), in line with previous reports 11,12,21,41 . This family is widespread in the gut of the human population and it is generally associated with healthy phenotypes, even though their abundances positively correlate to the intestinal transit time 59 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the most abundant taxa in PD there were bacteria belonging to the Christensenellaceae family (Fig 5, Supplementary Figure 10, 11), in line with previous reports 11,12,21,41 . This family is widespread in the gut of the human population and it is generally associated with healthy phenotypes, even though their abundances positively correlate to the intestinal transit time 59 .…”
Section: Discussionsupporting
confidence: 90%
“…The fact that the more abundant genera in PD belong to different families and even orders, support the idea of increased diversity in the gut-microbiota of PD patients (Fig 1, Supplementary Figure 1). The genus Lactobacillus , and the Lactobacillaceae family, were the most strongly enriched taxa in PD across the studies we re-analyzed, in line with previous findings 11,12,17,19,41 . Lactobacillus strains are low abundant members of the gut microbiota and their abundance varies greatly across human disease and chronic conditions 42 .…”
Section: Discussionsupporting
confidence: 90%
“…The study reported 9 metabolites to have the potential to be significantly altered in PD patients compared to healthy controls including methionine and cysteinylglycine, which are part of sulfur metabolism. Furthermore the authors showed that a higher presence of Akkermansia muciniphila, and Bilophila wadsworthia in PD patients, and identified a new research target in PD research with the use of metabolic networks [87]. Hertel et al confirmed these results by using the same approach as Baldini et al [87] to construct and simulate personalized community networks of 31 early stage, drug naïve PD patients and 28 age matched controls from data obtained from Bedarf et al [88].…”
Section: Simulation Of Dysbiosis and Treatment Using Metabolic Networkmentioning
confidence: 93%
“…The study reported 9 metabolites to have the potential to be significantly altered in PD patients compared to healthy controls including methionine and cysteinylglycine, which are part of sulfur metabolism. Furthermore the authors showed that a higher presence of Akkermansia muciniphila, and Bilophila wadsworthia in PD patients, and identified a new research target in PD research with the use of metabolic networks [ 87 ]. Hertel et al .…”
Section: Simulation Of Dysbiosis and Treatment Using Metabolic Networmentioning
confidence: 99%
“…This finding further highlights the inverse correlation between relative AM abundance in the colon and dietary fiber intake. Of note, increased abundances of AM were found to be associated with various pathologies in human studies [12][13][14][15][16][17], supporting the idea that, besides promoting microbiota-mediated SCFA production, fiber supplementation considerably contributes to maintenance of mucosal barrier integrity by preventing from excess mucus degradation.…”
Section: Origin Of Fimentioning
confidence: 63%